Enhancing clinical skill development through an Ambulatory Medicine Teaching Programme: An evaluation study. (6th June 2013) - Latta, L.; Tordoff, D.; Manning, P.; Dent, J.
Abstract : Background : Teaching of clinical skills traditionally takes place in hospital wards and outpatient settings. However high acuity and short hospital stays means there are fewer suitable inpatients available for teaching; and time pressures limit students' involvement in other settings. The Ambulatory Medicine Programme was established to develop undergraduate medical students' clinical skills by providing increased exposure to patients with a wide range of chronic medical conditions, in a dedicated learning environment. Method : A mixed qualitative/quantitative approach was used to evaluate the Programme. This research focuses on staff and student perspectives of teaching and learning in Ambulatory Medicine compared with inpatient and outpatient settings; identifies which teaching methods are considered most effective; and determines the transferability of learning. Patients' perspectives of being involved in student teaching are also reported. Results : Results show that the programme has made a positive impact on students' development of clinical skills, which are transferable to the clinical setting. Patients enjoy being involved and find it personally satisfying. Conclusions : The Ambulatory Medicine Programme is an effective way of developing medical students' clinical skills by providing focussed teaching with real patients in a dedicated learning environment.